Development and Evaluation of an Electronic Prototype for Pedagogical Skills Enhancement of Educators in Malaysian Higher Learning Institutions - Navamoney D.M, Amutha (2018)
This study was aimed at investigating how electronic learning prototype could be employed as an alternative training support of educators in Malaysian higher education for improving their pedagogical knowledge and skills. It explores the benefits of e-learning platform to facilitate higher learning educators and to mitigate growing challenges faced by educators in enhancing their pedagogical skills. The theoretical framework model of this study was guided by constructivism and connectivism learning theories along with activity theory and other theories such as adult learning theory, experiential and transformation theory. The activity theory guided the design-based research (DBR) by Reeves (2000, 2006) which is adapted in this study as its research methodology. This design-based research is carried out in eight phases: analysis, design, validation, development, implementation, evaluation, impact and continuous learning. The analysis and design phases obtain the perspectives of 8 experts comprises educators, manager, learning designers cum trainers and system administrator. In analyse phase the needs and challenges faced by educators in professional development for pedagogical skills enhancement were analysed and also identified the benefits and acceptance of an electronic prototype as an alternative solution for professional development. In design phase experts were to giving their inputs on learning strategies, elements, tools and system specifications for designing an electronic prototype. In validation and development phase, experts used ACTA techniques to validate the prototype. During the implementation and evaluation, 43 educators from higher education participated in the training course offered by the prototype. Two surveys were conducted immediately after the completion of the course. The result indicated that all educators agreed that they are ready and motivated to use technology in teaching and learning. Further, educators’ ii age, gender and teaching experience have no influence over their performance expectancy, effort expectancy and self-efficacy. However, the performance effort expectancy and self-efficacy have significant towards educators’ behavioural intention of using the prototype as self-directed and lifelong learning platform. The study also reported that the Secondary Influence, Environment and Ability variables have influence over the Motivation variables. Hence, electronic training can be scalable and sustainable alternative learning system for continuous professional development.